2015
DOI: 10.1186/1471-2105-16-s14-s4
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing a SuperGeneTree minimizing reconciliation

Abstract: Combining a set of trees on partial datasets into a single tree is a classical method for inferring large phylogenetic trees. Ideally, the combined tree should display each input partial tree, which is only possible if input trees do not contain contradictory phylogenetic information. The simplest version of the supertree problem is thus to state whether a set of trees is compatible, and if so, construct a tree displaying them all. Classically, supertree methods have been applied to the reconstruction of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The problem has been shown NP-hard for the duplication distance, and exponential-time algorithms have been developed for both distances. For segmental duplications only, the hardness of super-reconciliation is almost immediate from the results of [30]. For both duplications and losses, the problem remains NP-hard, although the proof is far more technical.…”
Section: Complexity Of the Super-reconciliation Problemmentioning
confidence: 97%
See 1 more Smart Citation
“…The problem has been shown NP-hard for the duplication distance, and exponential-time algorithms have been developed for both distances. For segmental duplications only, the hardness of super-reconciliation is almost immediate from the results of [30]. For both duplications and losses, the problem remains NP-hard, although the proof is far more technical.…”
Section: Complexity Of the Super-reconciliation Problemmentioning
confidence: 97%
“…, T k such that the LCAreconciliation of T and S yields a minimum number d of duplications. It was shown in [30] that it is NP-hard to approximate d within a factor n 1−ǫ for any 0 < ǫ < 1 , where here n is the number of genes in Ŵ = k i=1 L(T i ).…”
Section: Theoremmentioning
confidence: 99%
“…The M inSGT and M inLSGT problems for the duplication cost were both shown NP-Hard in [28], even in the case where no two input trees have a gene in common and the trees only contain speciations.…”
Section: Minimum Labeled Supergenetree (M Inlsgt ) Problemmentioning
confidence: 99%
“…In [28], we introduced under the name of MINIMUM SUPERGENETREE (M inSGT ) the problem of finding, for a set of gene trees, a supertree that minimizes the reconciliation cost with a given species tree. Under the duplication cost, we have shown that this problem is NP-hard to approximate within a n 1− factor, for any 0 < < 1, even for instances in which there is only one gene per species in the input trees, and even if each gene appears in at most one input tree.…”
Section: Introductionmentioning
confidence: 99%